2019
DOI: 10.1038/s41598-019-52555-1
|View full text |Cite
|
Sign up to set email alerts
|

Electrocortical Evidence for Impaired Affective Picture Processing after Long-Term Immobilization

Abstract: The neurobehavioral risks associated with spaceflight are not well understood. In particular, little attention has been paid on the role of resilience, social processes and emotion regulation during long-duration spaceflight. Bed rest is a well-established spaceflight analogue that combines the adaptations associated with physical inactivity and semi-isolation and confinement. We here investigated the effects of 30 days of 6 degrees head-down tilt bed rest on affective picture processing using event-related po… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 41 publications
2
18
0
Order By: Relevance
“…Previous research also found evidence for changes in emotional processing during a 30-day 6° HDBR study using event-related potentials (ERP), with an inhibition of P300 and late positive potential (LPP) components for emotional stimuli, but not neutral pictures, suggestive of emotional blunting ( Brauns et al, 2019 ). Messerotti Benvenuti et al (2013) likewise found emotional blunting in P300 and LPP components after only 3 h of 6° HDBR.…”
Section: Discussionmentioning
confidence: 88%
“…Previous research also found evidence for changes in emotional processing during a 30-day 6° HDBR study using event-related potentials (ERP), with an inhibition of P300 and late positive potential (LPP) components for emotional stimuli, but not neutral pictures, suggestive of emotional blunting ( Brauns et al, 2019 ). Messerotti Benvenuti et al (2013) likewise found emotional blunting in P300 and LPP components after only 3 h of 6° HDBR.…”
Section: Discussionmentioning
confidence: 88%
“…In addition to exploring the relationship between circadian disruptions and sleep in future studies, it will also be important to identify the effects of circadian changes on behavior and cognition. Several studies have shown adverse effects of bed rest on brain function and cognitive performance ( Lipnicki and Gunga, 2009 ; Brauns et al, 2019 ; Friedl-Werner et al, 2020 ; Basner et al, 2021 ), mental health ( Liu et al, 2012 ; Stavrou et al, 2018 ), cardio-vascular changes ( Solbiati et al, 2021 ), and metabolic regulation ( Dandanell et al, 2016 ; Dirks et al, 2016 ) that can be associated with a lack of sleep ( Mullington et al, 2009 ; Anderson and Bradley, 2013 ; Goel et al, 2013 ). To mitigate the adverse neurophysiological and psychological effects associated with circadian disruptions, effective countermeasures are needed to maintain the entrainment of central and peripheral clocks.…”
Section: Discussionmentioning
confidence: 99%
“…The increase in amplitudes can be attributed to a compensatory process in the control group that enabled them to fi nger tap correctly. Other bed rest studies addressing VEPs lack or focus on other paradigms and later ERP components (e.g., P3; Brauns et al, 2019). Considering bed rest as a model for an accelerated form of aging (Timiras, 1994;Vernikos & Schneider, 2009), results on aging studies and P2 latency parameters are mixed; some studies have shown increased P2 latencies (Goodin et al, 1978;Iragui et al, 1993;Pfeff erbaum et al, 1979Pfeff erbaum et al, , 1980, whereas others have reported no signifi cant age-related changes (Amenedo & Díaz, 1998, 1999Zalar et al, 2015).…”
Section: Discussionmentioning
confidence: 99%